HOLARCHICAL FIELD THEORY. - Bowman, Kevin J. (Journal of Integral Theory & Practice, 2012)
Within the dualities of Integral Theory, Integral Scientific Pluralism synthesizes Integral Epistemological Pluralism and Integral Ontological Pluralism, as described by Sean Esbjörn-Hargens, alongside Ken Wilber's Integral Methodological Pluralism. Further crossing the zones of Integral Scientific Pluralism in this article allows for an integration of the holarchcial drives described in my earlier work. This helps create Holarchical Field Theory, wherein holarchically embedded subjects and objects, motivated by their needs, become engaged through their interpenetrating drives. Various field theories in the social sciences help define Holarchical Field Theory for analyzing action while also inspiring the art of applying it in potential, future applications. The theory is then used to describe how it may overcome limitations in Wilber's current use of Integral Mathematics